Key Performance Indicators Implementation: Literature Review and Development for Performance Measurement - Welly Atikno; Indra Setiawan; Deni Ahmad Taufik (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
Recently a Key Performance Indicators (KPIs) performance measurement tool is developing very rapidly. KPIs have a very important meaning for a company. This paper aims to identify KPIs and classify them based on different perspectives such as publication by region, publication of industrial sector, publications by years, benefits implementing and development for perfomance measurement. This research is based on a literature review of artikel based on KPIs in the European region between 2015-2020. The implementation of these KPIs can be implemented in many organizations, such as manufacturing, service, health and research. KPIs can provide changes to an organization that implements them. KPIs themselves can be distinguished in many ways. There are KPIs for information technology, finance, maintenance management, production processes, design dan PPIC. This paper provides benefits for further research to increase literature and understanding regarding the implementation of KPIs.